2016
DOI: 10.1016/j.jagp.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of a Gain-Focused Reappraisal Intervention for Dementia Caregivers: A Double-Blind Cluster-Randomized Controlled Trial

Abstract: Objectives:To examine the effects of a benefit-finding intervention, the key feature being the use of gain-focused reappraisal strategies to find positive meanings and benefits in caring for someone with dementia. Design: Cluster-randomized double-blind controlled trial. Setting:Social centers and clinics. Participants: 129 caregivers. Inclusion criteria were (a) primary caregiver aged 18+ and without cognitive impairment, (b) providing ≥14 care hours per week to a relative with mild-to-moderate Alzheimer's di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
82
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 33 publications
3
82
0
Order By: Relevance
“…For that reason, intentional interventions by professionals are necessary to improve positive appraisal among caregivers. Previous studies reported that interventions focusing on positive appraisal were successful in improving the same as well as in reducing caregiver burden . However, despite the existence of many such interventions with promising results, they have not yet been widely implemented in clinical practice .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For that reason, intentional interventions by professionals are necessary to improve positive appraisal among caregivers. Previous studies reported that interventions focusing on positive appraisal were successful in improving the same as well as in reducing caregiver burden . However, despite the existence of many such interventions with promising results, they have not yet been widely implemented in clinical practice .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that interventions focusing on positive appraisal were successful in improving the same as well as in reducing caregiver burden. 7,38 However, despite the existence of many such interventions with promising results, they have not yet been widely implemented in clinical practice. 39 As such, we thought it also necessary to consider providing brief interventions that focus on caregiver burden and positive appraisal to family caregivers, as such assistance might be more feasible for clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…This also implies more attention to outcomes other than burden and depression, especially positive outcomes such as mastery and QoL. Other positive outcomes such as positive aspects of caregiving [84,85] also deserve more attention given their relevance to caregivers' functioning.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Thus, besides reflecting on their experiences and coming up with personally relevant benefits, participants were given hypothetical caregiving situations and were asked to come up with as many positive reappraisals as possible. 5,8,9 For example, when discussing particular neuropsychiatric symptoms, scenarios were presented about different fictitious caregivers frustrated by some symptoms and participants would be asked to "help" them by offering alternative appraisals. To consolidate learning during training sessions, caregivers were asked to keep journals of positive appraisals up to three times a week, which were then shared during the next training session.In addition, participants were asked to examine how negative thoughts affect their motivation to provide care and how reappraisal can help sustain the motivation in the long…”
mentioning
confidence: 99%